Seakeeping analysis of a Malaysian fishing vessel - Mostofa Kamal, Md. Abu Hena (2007)
This thesis describes a comparative study of seakeeping analysis for a fishing vessel in Malaysia. Three different methods were used for the seakeeping analysis namely; full scale trial, model experiments and time domain simulation. The simulation program was developed at Universiti Teknologi Malaysia (UTM). In this study, a Malaysian fishing vessel was taken as the basis for the seakeeping analysis. In the full scale trial, the wave data were recorded by a wave buoy to obtain the wave spectra. The responses of the vessel were recorded by the Vessel Motion Monitoring System (VMMS) to obtain the motions response spectra. A scaled (1: 10.6) model was tested in the towing tank of the Department of Marine Technology, UTM to obtain the responses of the model in regular waves and Response Amplitude Operator (RAO) in irregular waves. Roll decay tests were also conducted to obtain the roll natural frequency, damping coefficient and the position of center of gravity (KG) of the model. The time domain simulation program was used to obtain the sixdegrees of freedom motions of the vessel both in regular and irregular waves. Finally, the RAO and the responses obtained from the three different methods were compared. The Root Mean Square (RMS) values obtained from the responses were used to assess the seakeeping performance of the vessel. The results indicated that the measured wave spectrum is similar to that of the Pierson-Moskowitz spectrum. This is a good indication for ship designers to use the spectrum in the absence of actual wave data. The RMS values from simulation and measured methods (model test and full scale trial) indicated that they are in good agreement except for pitching motion. The disagreement in pitching motion is mainly due to the effect of non-linear coupling motions. Generally, from the comparison, it can be concluded that the developed ship simulation program could be used to predict seakeeping behaviour of fishing vessels operating in Malaysian waters.